2005
DOI: 10.1038/sj.gene.6364275
|View full text |Cite
|
Sign up to set email alerts
|

Examination of seven candidate regions for multiple sclerosis: strong evidence of linkage to chromosome 1q44

Abstract: Multiple sclerosis (MS) is a debilitating neuroimmunological and neurodegenerative disease with a strong genetic component. Numerous studies have failed to consistently identify genes that confer disease susceptibility except for association with HLA-DR. Seven non-HLA regions (1q, 2q, 9q, 13q, 16q, 18p and 19q) identified in a recent genomic screen were investigated by genotyping B20 single-nucleotide polymorphisms (SNPs) at B1 Mb intervals. Non-parametric multipoint analyses identified a peak LOD* score of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Molecular mechanisms leading to migration of autoreactive T cells from the bloodstream involve a series of sequential and overlapping interactions among different families of adhesion molecules, including selectins [2]. The selectin gene cluster maps to chromosome 1q23-25, close to regions previously associated with MS [3,4]. This information supports the notion that the selectin gene cluster is a good positional and functional candidate for MS. Several variants have been described in selectin genes.…”
supporting
confidence: 59%
“…Molecular mechanisms leading to migration of autoreactive T cells from the bloodstream involve a series of sequential and overlapping interactions among different families of adhesion molecules, including selectins [2]. The selectin gene cluster maps to chromosome 1q23-25, close to regions previously associated with MS [3,4]. This information supports the notion that the selectin gene cluster is a good positional and functional candidate for MS. Several variants have been described in selectin genes.…”
supporting
confidence: 59%
“…We analyzed SNPs in a ~ 7.0-Mb region of human 1q43 that showed suggestive linkage to multiple sclerosis (MS) [15,16]. This region was bounded by SNPs rs10925296 and rs1319790 (encompassing chr1:233,515,650-240,494,277 of human Build 35).…”
Section: Resultsmentioning
confidence: 99%
“…We have formulated a systematic approach to prioritize SNP markers to be genotyped for association studies in any target region, with a specific application to the 1q43 linkage region in MS [15,16]. This approach incorporates MCS analysis to prioritize markers within MCSs, termed MCS-SNPs, for high-throughput genotyping.…”
Section: Introductionmentioning
confidence: 99%
“…A combined genomic map of MS was constructed using 170 microsatellite markers or regions previously reported in whole genome linkage screens 2-14 and their follow-up studies, [20][21][22][23][24][25] and 263 'top-ranked' markers reported in the case-control association studies of the GAMES project. 15 These markers or regions were selected based on the statistics reported in the original studies, including both significant and suggested occurrences.…”
Section: Resultsmentioning
confidence: 99%